2015
DOI: 10.1007/s12539-015-0101-3
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Determination of the pK a Values of Betalamic Acid Related to the Free Radical Scavenger Capacity: Comparison Between Empirical and Quantum Chemical Methods

Abstract: Health benefits of dietary phytochemicals have been suggested in recent years. Among 1000s of different compounds, Betalains, which occur in vegetables of the Cariophyllalae order (cactus pear fruits and red beet), have been considered because of reducing power and potential to affect redox-modulated cellular processes. The antioxidant power of Betalains is strictly due to the dissociation rate of the acid moieties present in all the molecules of this family of phytochemicals. Experimentally, only the pK avalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…In fourth step (L 3-+ H + ⇄ HL 2-) which occurs around pcH =7-9.5, proton is added to the the phenolic group that is attached to C6 atom. These processes for deprotonation of betanin have been extensively studied by several researchers and some of them have demonstrated that two deprotonation reactions (second and third steps) are so close together and therefore, both of them can be assigned only to one reaction equilibrium [24]. In this research work, the obtained protonation constants are in fine agreement with those previously reported [20].…”
Section: Resultssupporting
confidence: 90%
“…In fourth step (L 3-+ H + ⇄ HL 2-) which occurs around pcH =7-9.5, proton is added to the the phenolic group that is attached to C6 atom. These processes for deprotonation of betanin have been extensively studied by several researchers and some of them have demonstrated that two deprotonation reactions (second and third steps) are so close together and therefore, both of them can be assigned only to one reaction equilibrium [24]. In this research work, the obtained protonation constants are in fine agreement with those previously reported [20].…”
Section: Resultssupporting
confidence: 90%
“…In contrast with flavonoids, however, the chemistry of the antioxidant mechanism of betalains is less understood. It has been suggested that the common skeleton betalamic acid may contribute to their antioxidant activities [57][58][59]. Phenolic hydroxy group in cyclo-dopa moiety of betacyanin and the amino acid/amine portion of betaxanthin may increase the radical scavenging activities of betalamic acids [58].…”
Section: Antioxidant Functions Of Betalainsmentioning
confidence: 99%
“…Also, in both cases, the S 0 ⟶S 1 transitions are well behaved, showing p-p* character and involving exclusively HOMO-LUMO transitions. We also calculated the pK a of the acidic groups in Bn using the empirical method implemented in MarvinSketch, which has been used to estimate the pK a of betalamic acid (76). This method predicts the CO 2 H group at C2 to be the most acidic (pK a 1.5), followed by the carboxylic groups at C17 (pK a 3.0) and C15 (pK a 3.7) and the 5-OH group (pK a 8.5), agreeing with the experimental values.…”
Section: Effects Of Ph and Temperature On The Rate Of Hydrolysis Of Bmentioning
confidence: 99%